The Comparison Between successful and unsuccessful countries in PISA 2009 - (:unkn) unknown (ELSEVIER SCIENCE BV, 2014)
This paper examines the performance of countries, which attended on the Programme for International Student Assessment (PISA) 2009 on mathematic literacy. The paper discusses Qatar, Kyrgyzstan, and Brazil's education system. It examines successful and unsuccessful countries PISA 2009 academic performance in mathematics literacy among 15 year olds students. The paper gives a better and deeper understanding of the relationship between countries success with educational reform, social, political, and economical aspects on students' academic performance in PISA. (C) The Authors. Published by Elsevier Ltd. Selection and/or peer-review under the responsibility of Academic World Education and Research Center.
Keywords: The Programme for International Student Assessment (PISA) 2009; mathematical literacy; education system; teacher training